A Survey of Teenagers' Attitudes Toward Moving Oral Contraceptives Over the Counter. Issue 3 (22nd June 2015) - Manski, Ruth; Kottke, Melissa
<x xml:space="preserve">Abstract</x> CONTEXT Evidence suggests that over‐the‐counter access to oral contraceptives may help expand use among adult women. Teenagers may particularly benefit from this approach, as they experience disproportionately high rates of unintended pregnancy and face unique challenges accessing contraceptives. However, limited research has explored teenagers' attitudes toward over‐the‐counter access. METHODS In 2014, a sample of 348 females aged 14–17, recruited via Facebook advertisements, participated in an online survey assessing teenagers' attitudes toward over‐the‐counter access and their understanding of how to use oral contraceptives after reading a prototype over‐the‐counter product label. Differences by participants' characteristics were assessed in bivariate analyses (Pearson chi‐square and Fisher's exact tests for categorical measures, and independent t tests and one‐way analyses of variance for continuous measures). RESULTS Seventy‐three percent of participants supported over‐the‐counter access, and 61% reported that they would likely use oral contraceptives available through this approach. Few subgroup differences were found. Notably, sexually experienced participants were significantly more likely than others both to support this approach (85% vs. 63%) and to be interested in obtaining oral contraceptives this way (77% vs. 48%). Participants understood an average of 7.1 of eight key concepts that the prototype product label was intended to convey; no significant differences were found among subgroups. CONCLUSIONS Over‐the‐counter access may be a promising approach for providing oral contraceptives to teenagers. Additional research is needed to evaluate whether teenagers can screen themselves for contraindications to oral contraceptive use and correctly use oral contraceptives obtained over the counter.